2020
DOI: 10.3126/jpan.v9i2.36288
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence And Correlates Of Delirium tremens In Alcohol Dependence Syndrome At Tertiary Hospital

Abstract: Introduction: The prevalence of Delirium tremens (DT) is around 5-12%. Very few studies have looked into the prevalence of DT in general population and has shown varying results. The study aims at finding the prevalence of delirium tremens among alcohol dependents (AD) and a comparison of profiles of alcohol withdrawal syndrome (AWS) with DT and AWS without DT. Material And Method: A case- control study was conducted in patients diagnosed as Alcohol dependent syndrome and admitted in Psychiatry in-patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The higher number of abs nent a empts could be because of the need for treatment the physical condi ons then as many had medical comorbidi es. Studies revealed that the average dura on of alcohol use was 20 and 24.8 years which is similar to ours with a median 14,16 dura on of 22 years. A longer dura on of alcohol intake 29 causes hyper excitability in the brain resul ng in DT.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The higher number of abs nent a empts could be because of the need for treatment the physical condi ons then as many had medical comorbidi es. Studies revealed that the average dura on of alcohol use was 20 and 24.8 years which is similar to ours with a median 14,16 dura on of 22 years. A longer dura on of alcohol intake 29 causes hyper excitability in the brain resul ng in DT.…”
Section: Discussionsupporting
confidence: 89%
“…In the study by Sarkar et al, Indian-made foreign liquor was most commonly 25 consumed. In studies from Nepal and our pa ents 14,16 consumed homemade (89.04%) alcohol.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These studies helped identify high-risk patients who developed DT. The demographic profile of these populations typically consisted of middle-aged males with comorbidities and a history of long-term alcohol abuse [40][41][42][43][44][45][46]. Efforts should be directed toward prevention, early intervention, and long-term treatment of alcohol dependence to reduce the burden of DT and associated complications.…”
Section: Discussionmentioning
confidence: 99%